2015
DOI: 10.3174/ajnr.a4259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 4D Vascular Flow and Tissue Perfusion in Cerebral Arteriovenous Malformations: Influence of Spetzler-Martin Grade, Clinical Presentation, and AVM Risk Factors

Abstract: BACKGROUND AND PURPOSE:The role of intracranial hemodynamics in the pathophysiology and risk stratification of brain AVMs remains poorly understood. The purpose of this study was to assess the influence of Spetzler-Martin grade, clinical history, and risk factors on vascular flow and tissue perfusion in cerebral AVMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Kim et al [25] showed that the efficacy of high-grade CAVM treatment was in relation to the lesion size, deep perforator artery, and bleeding during surgery. Besides, another study exhibited that the efficacy of CAVM treatment was related to the lesion volume, SM grade, and CAVM size, and that SM grade was an independent influencing factor [26, 27]. It has also been confirmed that CAVM size affects hemodynamic changes such as BFV and PI, that is, the increase in the size of CAVM led to the upsurge of average BFV and a decline in PI [20].…”
Section: Discussionmentioning
confidence: 94%
“…Kim et al [25] showed that the efficacy of high-grade CAVM treatment was in relation to the lesion size, deep perforator artery, and bleeding during surgery. Besides, another study exhibited that the efficacy of CAVM treatment was related to the lesion volume, SM grade, and CAVM size, and that SM grade was an independent influencing factor [26, 27]. It has also been confirmed that CAVM size affects hemodynamic changes such as BFV and PI, that is, the increase in the size of CAVM led to the upsurge of average BFV and a decline in PI [20].…”
Section: Discussionmentioning
confidence: 94%
“…9 205,206 . The findings showed that 4D flow MRI can assess treatment-induced changes in cerebrovascular flow distribution and were able to demonstrate significant associations between 4D flow metrics, cerebral perfusion indices, and AVM risk factors such as the Spetzler–Martin grade 206 .…”
Section: Applicationsmentioning
confidence: 99%
“…4D flow MR imaging has the ability to provide a comprehensive evaluation of intracranial hemodynamics, which has the potential to provide guidance to clinicians in the evaluation of intracranial aneurysms [14], plaque [5,6], arteriovenous malformations [7,8], and cerebral veins [9,10]. Due to the small lumen diameter, intracranial MRI requires a relatively high spatial resolution resulting in long scan times even for limited coverage.…”
Section: Introductionmentioning
confidence: 99%